Expression of microtubule-associated protein 2 by reactive astrocytes. - Geisert, E E (1990)
After an injury to the central nervous system, a dramatic change in the astrocytes bordering the wound occurs. The most characteristic feature of this process, termed reactive gliosis, is the upregulation of the intermediate filament protein, glial fibrillary acidic protein. In the present study, we show that reactive astrocytes express high levels of microtubule-associated protein 2 (MAP-2), a protein normally found in the somatodendritic compartment of neurons. When sections of injured brain are double-stained with antibodies directed against MAP-2 and glial fibrillary protein, all of the reactive astrocytes are found to contain MAP-2. The high levels of this protein appear to represent a permanent change in reactive astrocytes. In parallel quantitative studies, an elevated level of MAP-2 in the injured brain is confirmed by an immunoblot analysis of injured and normal white matter. This report demonstrates the direct involvement of a microtubule protein in the process of reactive gliosis.